Cardiac rehabilitation and prescription exercise training for heart failure’s patients - Fathurohim, Zainal; Tjahjono, Cholid Tri (Universitas Brawijaya, 2024)
Cardiovascular rehabilitation is a multidisciplinary approach that includes exercise instruction, reduction of cardiac risk factors, psychosocial assessment, and result evaluation. Cardiovascular rehabilitation (CR), which includes exercise training, has been shown to significantly improve people with heart failure's quality of life, functional ability, and hospitalizations for heart failure-related conditions. There are so many benefits that are crucial for patients that they must be implemented fully in every health center. The objective for all healthcare practitioners must be to include CR in the regular, normal management of HF patients.